WHAT CHANGES IN IMPLEMENTING COMPETENCE-BASED MEDICAL EDUCATION IN INDONESIA: A QUALITATIVE STUDY - Titi Savitri Prihatiningsih; Hikmawati Nurokhmanti; Geraldine Baujea (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2021)
Background: Competence-based Medical Education (CBME) is the latest curriculum model adopted by many countries since 1970s. Reforming medical curriculum to adopt CBME implicates major changes in all aspects and research on this is still lacking. This study aims at identifying changes in implementing CBME from the aspects of organization and structural changes, curricular design, implementation and evaluation and cultural changes. Methods: Retrospective qualitative method is applied using purposive sampling. Selected documents are used as the data and analysed using thematic analysis. Results: Four themes are identified for the first aspect, i.e. the role of central authority, multidepartment committees, committed change agents, and decision-making procedures. Whereas for the second aspect, five themes are pinpointed, consisting of curriculum design at macro level, meso and micro level, faculty development program, learning resources, implementation, and monitoring and qualitative evaluation. For the third aspect, four themes emerge, namely enabling factor, inhibiting factor, the paradox of the new curriculum and quality assurance. Conclusion: Major changes taking place in the design and implementation of CBME have been identified from three aspects inductively. Awareness of the kinds of changes and using them for curriculum planning could improve the success in shifting towards CBME.